PELANGGARAN HAK ASASI MANUSIA DALAM KERUSUHAN DI STADION KANJURUHAN MALANG BERDASARKAN HUKUM HAK ASASI MANUSIA: Violation of Human Rights in the Riot at Kanjuruhan Stadium Malang Based on Human Rights Law - Farhan Ananda Putra; Reni Dwi Purnomowati (Reformasi Hukum Trisakti, 2024)
A football match on October 1, 2022 at the Kanjuruhan stadium in Malang ended in a riot. Related to this, the security forces used tear gas to overcome the riots, but allegedly due to the excessive use of tear gas, it resulted in the loss of 135 lives in the stadium. The large number of casualties certainly raises issues regarding human rights. The problems to be examined in this article are whether there was a violation of human rights in the riot at Kanjuruhan stadium and how is the recovery of victims of the riot at Kanjuruhan stadium based on human rights law. This article is a normative legal research, descriptive in nature, then using primary and secondary data. Conclusions are drawn using the deductive method. Result and concludes that there was a violation of human rights to the right to life of people who were in the stadium during security that led to the loss of hundreds of lives. Recovery of the victims of the riot at the Kanjuruhan stadium in Malang was carried out by the government through Kemenkopolhukam by providing money of IDR 50 million for each victim who died and free health services for the injured.